Argentina : Third Review under the Stand-By Arrangement, Request for Waivers of Applicability of Performance Criteria, Financing Assurances Review, and Request for Modification of Performance Criteria-Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses Argentina's Third Review under the Stand-By Arrangement, Request for Waivers of Applicability of Performance Criteria, Financing Assurances Review, and Request for Modification of Performance Criteria. Discussions centered on the risks to the fiscal position, how best to counter the rise in inflation and inflation expectations, how best to mitigate debt rollover risks, and what more can be done to mitigate the impact of the economic downturn on the most vulnerable. The paper highlights that the Argentina economy continues to contract, albeit at a modestly slower pace than had been expected under the program. After a brief period of falling monthly inflation, price pressures and inflation expectations are again rising. Financial conditions improved in January, with declining sovereign spreads and a rally in the local equity market, but have since then erased much of those gains, with rising volatility in both currency and interest rates in March. All end-March performance criteria and fiscal targets are expected to be met.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet